Outbreak of NDM-1-producing Klebsiella pneumoniae in a neonatal unit in Colombia (2013)
Six multiresistant, NDM-1-producing Klebsiella pneumoniae strains were recovered from an outbreak that affected six neonatal patients in a Colombian hospital. Molecular analysis showed that all of the isolates harbored the blaNDM-1, qnrA, and intI1 genes and were clonally related. Multilocus sequence typing showed that the isolates belonged to a new sequence type (ST1043) that was different from the sequence types that had previously been reported. This is the first report of NDM-1-producing isolates in South America.